2018
DOI: 10.4103/sja.sja_385_17
|View full text |Cite
|
Sign up to set email alerts
|

Does neck circumference help to predict difficult intubation in obstetric patients? A prospective observational study

Abstract: Background:Failed intubation in obstetrics remains the most common cause of death directly related to anesthesia. Neck circumference has been shown to be a predictor for difficult intubation in morbidly obese patients. The aim of this study was to determine an optimal cutoff point of neck circumference for prediction of difficult intubation in obstetric patients.Methods:Ninety-four parturients scheduled for cesarean section under general anesthesia were included in the study. Preoperative airway assessment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
“…We identified further studies from references of retrieved articles and used citation tracking in Science Citation Index. The search was updated in March 2018 but we have not incorporated the results from 27 studies in this review.…”
Section: Methodsmentioning
confidence: 99%
“…These findings support that the NC and TMHT may be predictors of DL. Several studies showed promising results, even with a single predictor [4,[16][17][18][19][20][21][22]. However, the previous studies are different from those of ours.…”
Section: Discussionmentioning
confidence: 74%
“…The vast majority of the studies on prediction of difficult airway using NC is on obese patients so data in non-obese are insufficient [8,16,17]. There were also differences in the primary outcome (difficult intubation vs. DL) [8,18,[20][21][22]. There may be differences in some TMHT studies because the patient population is of different races from the patient population in our study.…”
Section: Discussionmentioning
confidence: 83%
“…In a general population, prediction of difficult intubation and mask ventilation is very insensitive and poorly specific [152], and combined tests add little to single tests [141]. In the general obstetric population, the factors associated with difficult intubation appear to be the same as for non-pregnant patients, including high Mallampati score, short neck, receding mandible, protruding maxillary incisors [153] and increased neck circumference [154]. Potential difficulties with mask ventilation were explicitly considered in some case reports, usually leading to a decision for awake intubation.…”
Section: Airway Assessment / Definitionmentioning
confidence: 99%